Dealing with Disruptive Behaviour of Students through Cooperative Learning Technique in Classrooms - Singh, Vandana (JOURNAL OF INDIAN EDUCATION, 2019)
Demographic and socio-economic shifts in nation’s population and changes in the family structure have placed increasing demands on the schools. There is a pressing need to understand the factors that give rise to and maintain aggressive behaviours among adolescents and also suggest techniques for dealing with the increased incidence of aggression and violence. FrustrationAggression theory by Dollard et al. in 1939, pointed out that if the goal directed behaviour is blocked, it leads to frustration which acts as the motive for aggression. Fear of punishment or disapproval may cause the aggressive behaviour to be displaced against some other target, or on oneself. In the classrooms, teachers can structure the learning goals which can promote cooperative, competitive or individualistic efforts. If one compares the cooperative situations with competitive situations,where students work against each other to achieve the goal, only one or few can attain the learning goal, whereas in cooperative situations, all the group members strive to achieve a common goal. ‘In the competition, there is negative interdependence among the goal achievements; students perceive that they can obtain the goals if and only if other students in the class fail to obtain their goals’ (Deutsch, 1949; Johnson and Johnson, 1989). This paper discusses how the technique of cooperative learning can prove useful to overcome the root cause of conflict, aggression, and intolerance, which develops in the students. By adopting the cooperative learning technique, a teacher can create a positive interdependence among the students for accomplishing any learning goal.